Enantioselective Au‐Catalyzed Synthesis of Thia[5]‐ and Thia[6]helicenes and Their Transformation into Bowl‐shaped Pleiadenes. Issue 17 (17th March 2023) - Fu, Wei; Pelliccioli, Valentina; von Geyso, Moritz; Redero, Pablo; Böhmer, Christian; Simon, Martin; Golz, Christopher; Alcarazo, Manuel
Abstract: A series of helically shaped benzo[b]chryseno[4, 3‐d]thiophenes, naphtho[1, 2‐b]phenanthro[4, 3‐d]thiophenes, and chryseno[3, 4‐b]naphtho[1, 2‐d]thiophenes is synthesized via a highly enantioselective Au‐catalyzed intramolecular alkyne hydroarylation reaction. The inversion barriers of the structures obtained are determined both theoretically and experimentally, and their chiroptical properties are reported. Preliminary studies on the post‐synthetic functionalization of these thiahelicenes and their transformation into azahelicenes are also presented. In addition, a straightforward one‐step protocol is developed, which wraps the initially obtained chryseno[3, 4‐b]naphtho[1, 2‐d]thiophenes into bowl‐shaped pleiadene derivatives without erosion of the enantiopurity. The number of structurally related products that are obtained with high enantioselectivity enables the establishment of comprehensive correlations between the structure and conformational stability or (chir)optical properties. Abstract : The highly enantioselective synthesis of three families of thiahelicenes is described, their inversion barriers determined, and their photochemical characterization reported. Upon acidic treatment of thia[6]helicenes these structures are wrapped into bowl‐shaped pleiadenes with complete helical‐to‐point chirality transfer.